The clinical effect of sevoflurane anesthesia with laryngeal mask airway in the extraction of teeth in children - Wang, Bin; Han, Minglin (Frontiers in Pediatrics, 2024)
Objective: To evaluate the effect of sevoflurane general anesthesia with laryngeal mask airway in the extraction of teeth. Methods: A retrospective analysis was performed on 88 children who underwent extraction of teeth in the Department of Anesthesiology of our hospital from June 2022 to April 2023, including 44 patients who received traditional anesthesia as the control group and 44 patients who received laryngeal mask airway sevoflurane general anesthesia as the observation group. Anesthesia and operation records of patients in the two groups were analyzed, including intraoperative vital signs, anesthesia induction time, recovery time of spontaneous breathing, first feeding time within 24 hours after surgery, postoperative pain score, incidence of adverse reactions, Ramsay score and wake agitation, and other indicators were collected, and statistical analysis was conducted. Results: The recovery time of the observation group was 7.88±4.95 minutes, and the recovery time of spontaneous respiration was 10.58±3.64 minutes, which were significantly shorter than 15.23±5.12 minutes and 14.41±3.56 minutes of the control group (P<0.001). There were no significant differences between the two groups in anesthesia induction, operation duration and first feeding time within 24 hours after operation (P>0.05). There was no significant difference in postoperative pain scores between the two groups (P>0.05). The overall incidence of adverse reactions was 6.82% in the observation group compared with 22.73% in the control group (χ² = 4.423, P = 0.035). In addition, the Ramsay score of the observation group was significantly improved compared with the control group (P<0.05), and the incidence of agitation during the recovery period was also significantly decreased (P<0.05). Conclusion: Laryngeal mask airway sevoflurane anesthesia can significantly accelerate the recovery process of children after extraction of teeth, and reduce the occurrence of adverse reactions, providing a safer and more efficient choice than traditional anesthesia.